Legal challenges for school administrators and governors when school playgrounds become battlegrounds - Squelch, Joan; Wimbridge, G. (South African Education Law Association, 2009)
In 2009 a schoolyard fight at a secondary school watched by cheering students was videoed and posted on the Internet. This is one of many such incidents that provided the impetus for this paper and the issue of school violence. The focus of this paper is on the role and responsibilities of school principals and school councils (governing bodies) in Australia on managing and controlling student behaviour in the face of increasing incidents of school violence. Legal issues relating to the use of technology in relation to school violence and anti-social behaviour, such as cyber-bullying are also discussed. The paper highlights the very limited role of school councils; the lack of uniformity of policy across the various jurisdictions; and the complex procedures relating to suspension and expulsion. The paper concludes with a brief discussion on restorative justice as an alternative to punitive discipline strategies.